Integrating Generative AI in English Listening Instruction: A Multi-Perspective Analysis of Teacher and Students Perceptions - Teguh Putra Anugrah; Dedi Irwan; Rahayu Meliasari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The existence of artificial intelligence (AI) today can help teachers create contextual listening materials through tools like ChatGPT and Google AI Studio. This study aims to determine the perceptions of an English teacher and students regarding the use of AI in contextual listening materials. Employing a qualitative approach with a descriptive design, the research involved an English teacher and six students at State Junior High School 1 Balai. Data were collected through interviews and observations and analyzed using thematic analysis. The findings revealed that students perceived AI-generated contextual materials as significant for augmenting listening skill through clearer pronunciation and digestible content. The integration of local stories, such as "Mangkit hamlet," fostered higher engagement, enjoyment, and cultural relevance. From the teacher's perspective, GenAI served as a bridge to develop contextual materials efficiently, allowing for the customization of content to reflect students' daily lives and local heritage. Furthermore, collaboration with the researcher supported the teacher's professional competencies in navigating AI tools. Despite these benefits, challenges such as the need for stylistic audio refinements, teacher training, and stable infrastructure (internet and electricity) were identified as crucial factors for successful classroom integration.